2018
DOI: 10.1038/s41423-018-0042-y
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs in the metabolic control of inflammation and immune disorders

Abstract: The metabolic control of immune cell development and function has been shown to be critical for the maintenance of immune homeostasis and is also involved in the pathogenesis of immune disorders. Pathogenic infections or cancers may induce metabolic reprogramming through different pathways to meet the energy and metabolite demands for pathogen propagation or cancer progression. In addition, some deregulated metabolites could trigger or regulate immune responses, thus causing chronic inflammation or immune diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…Intriguingly, noncoding RNAs, especially snRNAs with stem-loop structures, can trigger TLR3 activation. 33,34 These results, together with previous reports, suggest that highly enriched noncoding RNAs in L-MPs are potential ligands that activate TLR3 signaling in macrophages. L-MPs induce mitochondrial ROS to activate NLRP3 for IL-1β cleavage Although activated TLR3 signaling can upregulate IL-1β mRNA expression and lead to the translation of pro-IL-1β, the production of mature IL-1β is mediated by inflammasome-activated caspase-1, which cleaves pro-IL-1β.…”
Section: M2-like Macrophages Induced By L-mps Upregulated Il-1β Expresupporting
confidence: 77%
“…Intriguingly, noncoding RNAs, especially snRNAs with stem-loop structures, can trigger TLR3 activation. 33,34 These results, together with previous reports, suggest that highly enriched noncoding RNAs in L-MPs are potential ligands that activate TLR3 signaling in macrophages. L-MPs induce mitochondrial ROS to activate NLRP3 for IL-1β cleavage Although activated TLR3 signaling can upregulate IL-1β mRNA expression and lead to the translation of pro-IL-1β, the production of mature IL-1β is mediated by inflammasome-activated caspase-1, which cleaves pro-IL-1β.…”
Section: M2-like Macrophages Induced By L-mps Upregulated Il-1β Expresupporting
confidence: 77%
“…Previous study showed that H19 could participate in the regulation of various biological processes such as cell proliferation, apoptosis and metabolism [25], and H19 was up-regulated in cirrhotic liver tissue [26]. H19 was also reported to be a lipid sensor by synergizing with polypyrimidine tract-binding protein 1 (PTBP1) to modulate hepatic metabolic homeostasis [12].…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a class of transcripts (longer than 200 nucleotides in length) without the function of encoding proteins [4]. LncRNAs have been shown to play essential roles in multiple biological processes [5–7]. In recent years, increasing evidences have demonstrated that dysregulation of lncRNA is closely associated with diverse diseases including OA [8–10].…”
Section: Introductionmentioning
confidence: 99%